Terror through the Looking Glass: Information Orientations and the Lens of Web Search Engines - Whyte, Christopher (Terrorism and political violence, 2024)
Researchers and pundits alike regularly describe terrorism as being a theatrical performance that depends on publicity to build recognition, garner attention and command legitimation. Clearly, the mechanical contours of the information environment matter when it comes to determining the opportunities and challenges for both terrorist and counterterrorist success. This article addresses arguably the most singularly significant intermediary for information access in modern society: web search engines. These information gatekeepers play a crucial role in guiding both government and non-state approaches to terror. That said, these tools are associated with bias and malperformance on a number of fronts. This study examines the degree to which different search engine usage might present a differential view of terrorism to different users. I turn to agent-based digital infrastructure as a basis for studying divergent information experiences with a major terrorist incident, specifically the suicide bombing and subsequent small arms attacks on the Hamid Karzai International Airport in Kabul, Afghanistan on August 26, 2021. The results are striking, confirming that there is substantial and clear variation in the outputs based around a host of factors—variable queries and query styles, information orientations and subsequent personalization, geographic location and, of course, search engine choice.